Comparative Economic Performance and Institutional Change in OECD Countries: Evidence from Subjective Well-Being Data - Heinz Welsch; Jan Kühling (University of Oldenburg, Department of Economics, 2011)
We use data on the subjective well-being (SWB) of more than 91,000 individuals in 30 member countries of the Organization for Economic Cooperation and Development (OECD) to assess the well-being effects of unemployment, inflation and national income growth. The relationships found are used to construct an index of national economic performance in terms of SWB. Applying the index to the period 1990-2009, we find that economic performance has improved in OECD overall and in the majority of countries, and that there has been a convergence of performance within the OECD. We then present evidence that OECD countries' economic performance, as measured, is positively related to institutional change towards more trade openness and better governance quality.
Keywords: E61; I31; F15; 330; economic performance; institutional change; trade; subjective well-being; OECD